Are we all in this together? Footballing ethics in the age of Coronavirus - Kampmark, B. (Soccer & Society, 2021)
The effects of COVID-19 have been telling in the sports world, seeing competitions suspended indefinitely. Initial optimism in England - that the Premier League would resume in May - dampened in favour of caution. In the absence of play and catastrophic economic losses, wealthy managers and executives have been encouraged, from a financial perspective, to accept wage freezes and reductions. Players have also been encouraged to do so as part of an effort in solidarity. This paper considers the ethical dimension of such gestures and how these have been received. How is the footballer, rendered physically incapable in such circumstances to prove sporting worth, to be critiqued? A new pandemic morality, it is argued, has emerged, one that takes an austere view of footballers and their conduct. Appraised as such, these figures are seen less as heroic beings than citizens engaged in a common cause and reviled for not doing so, a return, it is contended, to the principle of amateurishness. Specific reference is made to the English Premier League to illustrate the point.